A review of Mesotritia (Acari: Oribatida: Oribotritiidae) in China, with descriptions of two new species and a checklist of known taxa - Liu, Dong; Chen, Jun (Zootaxa, 2010)
The oribatid mite genus Mesotritia Forsslund, 1963 (Oribotritiidae) is reviewed. Five species of Mesotritia including two new species, Mesotritia bicarinata sp. nov. and Mesotritia serrata sp. nov., and three newly recorded species from China, M. maerkeli Sheals, 1965, M. nuda (Berlese, 1887) and M. okuyamai Aoki, 1980, are identified. A checklist of all known species and a key to the Chinese species of this genus are provided.